PENGARUH LINGKUNGAN KERJA, BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP MOTIVASI KERJA PEGAWAI PADA PT. SEMEN TONASA - Rego Devila (Jurnal Bisnis dan Kewirausahaan, 2017)
The results of this study are expected to expand the scientific study of human resource management, especially regarding work environment, organizational culture and organizational commitment to employee motivation PT. Semen Tonasa, so that the results of this study can provide insight and knowledge on how to improve employee motivation. Data used in this study are primary data that the questionnaire answers of respondents with data analysis using multiple linear regression using SPSS. Samples are 94 respondents employees of PT. Semen Tonasa. These results indicate the work environment, organizational culture and organizational commitment to employee motivation PT. Semen Tonasa. This suggests that the perceived better working environment of employees, and the stronger the culture of the organization, and the organization that exists optimalkomitmen the higher motivation of employees, the better. We recommend that the employees of PT. Semen Tonasa strive to continuously improve employee motivation at each task environment. This can be done by improving the work environment, organizational culture and organizational commitment, so as to improve the quality of human resources in it.